An Italian Retrospective Survey on Bone Metastasis in Melanoma: Impact of Immunotherapy and Radiotherapy on Survival - Mannavola, Francesco; Mandala, Mario; Todisco, Annalisa; Sileni, Vanna Chiarion; Palla, Marco; Minisini, Alessandro Marco; Pala, Laura; Morgese, Francesca; Di Guardo, Lorenza; Stucci, Luigia Stefania; Guida, Michele; Indini, Alice; et al. (Frontiers in Oncology, 2020)
Background We performed a multicenter retrospective observational study to investigate the impact of clinical–pathological features and therapeutic strategies on both the complications and survival of patients with bone metastases (BMs) from malignant melanoma. Patients and Methods A total of 305 patients with melanoma and radiological evidence of BMs were retrospectively enrolled from 19 Italian centers. All patients received conventional treatments in accordance with each own treating physician’s practice. Both univariate and multivariate models were used to explore the impact of melanoma features, including skeletal-related events (SREs), and different treatments on both overall survival (OS) and time-to-SREs. The chi-squared test evaluated the suitability of several parameters to predict the occurrence of SREs. Results Eighty-three percent of patients had metachronous BMs. The prevalent (90%) bone metastatic site was the spine, while 45% had involvement of the appendicular skeleton. Forty-seven percent experienced at least one SRE, including palliative radiotherapy (RT) in 37% of cases. No melanoma-associated factor was predictive of the development of SREs, although patients receiving early treatment with bone-targeted agents showed 62% lower risk and delayed time of SRE occurrence. Median OS from the diagnosis of bone metastasis was 10.7 months. The multivariate analysis revealed as independent prognostic factors the number of BMs, number of metastatic organs, baseline lactate dehydrogenase levels, and treatment with targeted therapy or immunotherapy. Subgroup analyses showed the best OS (median = 16.5 months) in the subset of patients receiving both immunotherapy and palliative RT. Conclusion Based on our results, patients undergoing immunotherapy and palliative RT showed an OS benefit suggestive of a possible additive effect. The apparent protective role of bone targeting agent use on SREs observed in our analysis should deserve prospective evaluation.